L’approche centrée sur le développement du pouvoir d’agir : aperçu de ses fondements et de son application - Le Bossé, Yann; Gaudreau, Lorraine; Arteau, Marcel; Deschamps, Kathy; Vandette, Line (Canadian Journal of Counselling and Psychotherapy, 2007)
An approach focused on the empowerment of people and groups is proposed as the basis for the development of more efficient social practices. This article provides a review of the premises on which this approach is based and the elements that characterize it. Secondly, the application of this approach is examined through the presentation of a concrete example. The authors conclude by drawing several general implications for the adoption of this approach at the level of interventions.